Pengembangan Program Edupreneurship dalam Menumbuhkan Jiwa Kewirausahaan di Sekolah Menengah Kejuruan - Wijayanti, Reny Widya; Tyas, Zuhriana Widya Rahayu Ning; Hikmawati, Hanifah (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2024)
The unemployment rate is still relatively high, and interest in entrepreneurship is still relatively low. It encourages schools to develop edupreneurship programs so that students have an entrepreneurial spirit and additional skills to prepare for life in the future. This research aims to determine various edupreneurship programs at Public Vocational High School (SMK Negeri) 1 Ngawi, the school principal's efforts in developing edupreneurship programs, and the factors inhibiting and supporting their development. This research uses a qualitative method that utilizes primary (interviews) and secondary data (documentation of activities and observations). The research results show three significant findings: First, SMK Negeri 1 Ngawi has five entrepreneurship programs: entrepreneurship lessons, P5, service unit, teaching factory, and industrial visits. Second, the school principal strives to develop edupreneurship programs per existing regulations, encourages teachers and students to participate in entrepreneurial activities, and evaluates ongoing activities. Third, inhibiting factors include policy regulations, lack of financial support, lack of consumers, and technological challenges. Meanwhile, the supporting factors are the students' willingness to become entrepreneurs, the existence of UPJ and teaching factories, and the strategic position of the school.